POLYCYSTIC OVARY SYNDROME: ROLE OF AROMATASE GENE VARIANTS IN SOUTH INDIAN WOMEN - K.RANJITH REDDY,; DEEPIKA M.L.N,; K.PRASANNA LATHA,; SAGURTHI.S.R,; LAKSHMANARAO S.S,; P. FAZUL RAHMAN,; JAHAN P, (International Journal of Pharma and Bio Sciences, 2015)
CYP19A1 gene encodes an aromatase enzyme that mediates the conversion of androgens to estrogens and appears to play a crucial role in the pathophysiology of Polycystic Ovary Syndrome (PCOS), a heterogeneous metabolic disorder that affects 4 - 12% women worldwide. We investigated the impact of an exonic, rs700519 and two intronic, rs2414096, rs60271534 variants of CYP19A1 gene by recruiting 506 subjects that include PCOS patients and non-PCOS controls from South India. The results indicate that all the three gene variants are associated significantly with disease susceptibility (p<0.05). However, multiple logistic regression analysis revealed a strong association of exonic variant (Arg264Cys) with the disease which was further supported by Multifactor Dimensionality Reduction analysis and In silico studies. Women with haplotype block A-C-L was observed to be in elevated frequency in non-PCOS group suggesting a significant protection against the disease. We conclude that women carrying the selected gene variants individually or in combination with exonic variant may have proclivity towards PCOS .The major role of Arg264Cys conversion projected could be due to destabilized structure of aromatase near substrate recognition site 3 that may reduce enzyme activity. To support the present results, characterization of these gene variants in diverse ethnic groups under different environmental backgrounds through biochemical and In silico approaches are warranted.